Development of a Framework for Lean Education Implementation in Vocational High Schools - Parestri, Kartikaratri Dewi; Karningsih, Putu Dana (Tibuana, 2025)
Lean, which aims to eliminate waste, has been applied to manufacturing and non-manufacturing operations. Some studies reported lean applications improving operations in universities and high schools. This study aims to develop a framework for implementing Lean Education for vocational high schools (SMK). This research is motivated by various forms of waste in SMK operations, such as long waiting times. Combination of an exploratory qualitative approach, literature review and expert validation are utilized to construct a context-specific framework. The proposed framework consists of three main stages: pre-implementation, implementation, and post-implementation, each comprising key activities such as waste identification, staff training, process mapping, lean strategy execution, and continuous improvement. This framework is expected to support SMK in minimizing waste and aligning vocational education more closely with industry needs, thereby enhancing the quality of its graduates.